Pengaruh Work-Life Balance, Stres Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan di Perusahaan FnB: The Influence of Work-Life Balance, Work Stress and Work Discipline on Employee Performance in FnB Companies - Aliffah Wahyu Larasati; Laniyafi Rahili; Aditya Aditya; Fahmi Fahmi; Rani Sudrajat; Adrian Al Rizki; Barnas Karondeng; Rifkhan Rifkhan (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze the effects of work–life balance, job stress, and work discipline on employee performance in Food and Beverage companies. The FnB industry faces job demands that often trigger stress, reduced discipline, and imbalance between personal life and work. This research uses a approach with a survey method by distributing questionnaires to 43 respondents. The work–life balance variable is measured through indicators of time balance, involvement, and satisfaction. Job stress is measured through role ambiguity, career development, and work relationships. Work discipline is measured through punctuality, time utilization, compliance with rules, work targets, and work reports. Employee performance is analyzed through indicators of quality, quantity, timeliness, and work effectiveness. Research instruments were tested for validity and reliability, with all items declared valid and Cronbach’s Alpha values above 0.60. Data analysis was conducted using regression, t tests, F tests, and coefficient of determination. The results show that work–life balance has a significant effect on employee performance, job stress has no significant effect, while work discipline has a positive and significant effect. Simultaneously, the three independent variables significantly affect employee performance with a contribution of 48.1 percent, while the remaining percentage is influenced by other factors outside the research model.